Hønsegårdens tamme ørne: En analyse af fuglemotiver i Henrik Pontoppidans forfatterskab - Zeeberg Nielsen, Oliver (Pontoppidaniana, 2025)
Abstract Danish author Henrik Pontoppidan regularly makes use of symbolic images of birds, in his descriptions of characters, their ambitions and struggles. Through analysis of the three short stories “Ørneflugt”, “Naar Vildgæssene trækker forbi” and De vilde Fugle I argue that there is a general use of references to tame farm animals like ducks and geese on one hand and wild birds like migrating geese and eagles on the other hand. These two opposites represent an individual’s greatness of character or lack thereof. At the end I argue for how this system of thought can be used to better understand the often-discussed ending of Pontoppidans great novel Lykke-Per.